Autumn migration tracks of Helopsaltes grasshopper‐warblers from Northeast Asia support recent taxonomic assignments. Issue 3 (23rd March 2023) - Sleptsov, Yuri; Ktitorov, Pavel; Round, Philip D.; Heim, Wieland
Abstract: Migration strategies are genetically inherited in most songbirds, and closely related species can exhibit markedly contrasting migration programs. Here, we investigate the autumn migration of one Helopsaltes grasshopper‐warbler from a population near Magadan, North East Russia, based on light‐level geolocation. Although often considered to belong to Middendorff's Grasshopper‐warbler H. ochotensis, recent genetic studies suggest that birds from this population are more closely related to Pallas's Grasshopper‐warbler H. certhiola . We compare the migratory behavior of the Magadan bird with two Pallas's Grasshopper‐warblers tracked from populations in the Kolyma River valley and the Amur region, Russia. We found similar migration patterns in all three tracked individuals, with stopover sites in eastern China and wintering sites in mainland Southeast Asia, within the known range for Pallas's Grasshopper‐warbler. Furthermore, based on morphological data compiled during bird ringing, we were able to confirm the presence of potential "Magadan grasshopper‐warblers" during spring and autumn migration in Thailand. Our scant data provide further evidence that Magadan Helopsaltes, notwithstanding their morphological resemblance to Middendorff's Grasshopper‐warbler, constitute a population of Pallas's Grasshopper‐warbler. Abstract : Here, we investigate the autumn migration of Helopsaltes grasshopper‐warblers from North‐East Russia based on light‐level geolocation. We found that individuals from the Magadan population showed similar migration patterns to Pallas's Grasshopper‐warblers, with stopover sites in eastern China and stationary sites during the boreal winter in Southeast Asia. Although limited to single individuals, our data provide further evidence that grasshopper‐warblers from Magadan should be included into Pallas's Grasshopper‐warbler and should not be treated as a subspecies of Middendorff's Grasshopper‐warbler.